A case report of secondary cutaneous cryptococcosis in a retrovirus positive patient - Yadhav, M L Kala; Samreen, Saba (Indian Journal of Case Reports, 2020)
Cryptococcosis is a systemic mycosis caused by the capsulated yeast Cryptococcus neoformans. Cryptococcus remains an important opportunistic pathogen in HIV positive patients. It is usually acquired through inhalation of spores and by invasion of the respiratory system, and then, the organisms may spread hematogenously to other viscera mainly central nervous system. Although there are some reports of primary cutaneous cryptococcosis, cryptococcal skin disease is a rare feature of disseminated cryptococcosis and has poor outcome if undiagnosed and untreated. We present a case of secondary cutaneous cryptococcosis in a 50-year-old male, who was diagnosed as a case of retroviral disease 3 years back but not on anti-retroviral therapy.